Osteoporotic Conditions Influence the Activity of Adipose-Derived Stem Cells - Park, Jeong Seop; Piao, Jiyuan; Park, Gabee; Yoo, Kyung Sang; Hong, Hyun Sook (Tissue Engineering and Regenerative Medicine, 2020)
Estrogen deficiency decreases bone density and increases the risk of osteoporosis and fracture, thereby necessitating reconstruction of bone regeneration. As bone marrow mesenchymal stem cell (BMSCs) lose viability and differentiation potential under osteoporotic conditions, it is impossible to use autologous BMSCs for osteoporosis treatment. As an alternative, adipose-derived stem cells (ADSCs) may serve as the source of therapeutic cells. We evaluated the effects of osteoporosis on the functional characteristics of ADSCs. Osteoporosis was induced in ovariectomy (OVX) rat model, and the ADSCs from Sham and OVX groups were cultured and analyzed comparatively. As a result, the viability was higher for the ADSCs from Sham group than those from OVX group. The analysis of the paracrine potential of ADSCs revealed the elevated levels of inflammatory and cellular senescence factors in the ADSCs from OVX group. The ADSCs from OVX group had much higher differentiation potential into adipocytes than those from the Sham group. Osteoporotic environment had no effect on the osteogenic potential of ADSCs. Osteoporosis may reduce the activity and influence immune response of ADSCs by modulating paracrine action and adipogenic potential. These characteristics of ADSCs should be given consideration for therapeutic purpose.